Failure Risk Analysis on Glass Bowl Products Using Failure Mode and Effect Analysis (FMEA) Method at PT. Kedaung Indah Can, Tbk - Artha Fitri Wulandari (abdimesin, 2025)
Kedaung Indah Can, Tbk is a manufacturer and exporter of canned/tin products and enamel steel cookware, one of which is glass bowls. During the production process, problems often arise, namely a fairly high level of product defects. These defects occur more often in the inspection process, namely the process before the product is handed over to consumers, the inspection section will check and test the product according to applicable standards and provisions. In this study, the author aims to identify the risks that occur so that they can produce high productivity and propose improvements in reducing defects. The method used to solve this problem is Failure Mode and Effect Analysis (FMEA) to determine the dominant failures that cause product damage and determine the priority of repairs from the results of the Risk Priority Number (RPN) value. The results of this study indicate that there are 3 types of defects that produce RPN values, including broken glass bowls with an RPN value of 192, cracked glass bowls with an RPN value of 125 and untidy bowl colors with an RPN value of 100.